Immune Checkpoints Expression in Chronic Lung Allograft Rejection - Righi, Ilaria; Vaira, Valentina; Morlacchi, Letizia Corinna; Croci, Giorgio Alberto; Rossetti, Valeria; Blasi, Francesco; Ferrero, Stefano; Nosotti, Mario; Rosso, Lorenzo; Clerici, Mario (Frontiers in Immunology, 2021)
Chronic lung allograft dysfunction (CLAD) is the main cause of poor survival and low quality of life of lung transplanted patients. Several studies have addressed the role of dendritic cells, macrophages, T cells, donor specific as well as anti-HLA antibodies, and interleukins in CLAD, but the expression and function of immune checkpoint molecules has not yet been analyzed, especially in the two CLAD subtypes: BOS (bronchiolitis obliterans syndrome) and RAS (restrictive allograft syndrome). To shed light on this topic, we conducted an observational study on eight consecutive grafts explanted from patients who received lung re-transplantation for CLAD. The expression of a panel of immune molecules (PD1/CD279, PDL1/CD274, CTLA4/CD152, CD4, CD8, hFoxp3, TIGIT, TOX, B-Cell-Specific Activator Protein) was analyzed by immunohistochemistry in these grafts and in six control lungs. Results showed that RAS compared to BOS grafts were characterized by 1) the inversion of the CD4/CD8 ratio; 2) a higher percentage of T lymphocytes expressing the PD-1, PD-L1, and CTLA4 checkpoint molecules; and 3) a significant reduction of exhausted PD-1-expressing T lymphocytes (PD-1pos/TOXpos) and of exhausted Treg (PD-1pos/FOXP3pos) T lymphocytes. Results herein, although being based on a limited number of cases, suggest a role for checkpoint molecules in the development of graft rejection and offer a possible immunological explanation for the worst prognosis of RAS. Our data, which will need to be validated in ampler cohorts of patients, raise the possibility that the evaluation of immune checkpoints during follow-up offers a prognostic advantage in monitoring the onset of rejection, and suggest that the use of compounds that modulate the function of checkpoint molecules could be evaluated in the management of chronic rejection in LTx patients.